OPEN GOVERNMENT PARTICIPATION (OGP) IN THE MANAGEMENT OF SPECIAL FINANCIAL ASSISTANCE FOR VILLAGES SOURCE OF FUNDS FOR THE REGIONAL REVENUE AND EXPENDITURE BUDGET OF RIAU PROVINCE - Ade Syaputra; Yunnie Armanda (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study analyzes the application of the principle of Open Government Participation (OGP) in the management of village-specific financial assistance sourced from the Riau Provincial Budget for 2023-2024. Using a qualitative approach with a focus on secondary data, this study explores the implementation of the principles of transparency, participation, and accountability. The results of this study show that the implementation of OGP varies; Transparency and participation show early progress but face challenges of information accessibility and substantive participation, while horizontal accountability requires strengthening. Overall, OGP has the potential to significantly improve village fund governance, although its implementation requires continuous improvement. OGP optimization is needed by increasing multi-stakeholder cooperation, especially with Universities and Non-Government Organizations (NGOs) so that the planning, implementation and benefits of the special financial assistance fund disbursement are wider and cause a multiplier effect.